Sinopsis del Derecho Universal. 1720 (Traducción del italiano y notas por Jose M. Sevilla, pp. 439-459). - Vico, G. (Cuadernos sobre Vico, 2020)
CUADERNOS SOBRE VICO, 9-10 (1998). 498 págs. ISBN 1130-7498